Anti‐mullerian hormone levels decline with the presence of antiphospholipid antibodies. (18th August 2016) - Vega, Mario; Barad, David H.; Yu, Yao; Darmon, Sarah K.; Weghofer, Andrea; Kushnir, Vitaly A.; Gleicher, Norbert
Abstract : Problem: Autoimmunity is thought to be an important cause of premature ovarian senescence, characterized by abnormal ovarian reserve markers. Anti‐Mullerian hormone (AMH) has emerged as the most reliable marker for ovarian reserve. We here investigated whether non‐specific immune markers are associated with a low age‐specific AMH. Method of study: To test the hypothesis that autoimmunity may predispose to low AMH, we investigated in 351 female infertile patients whether panels positive for non‐specific immune tests (antinuclear antibody, antiphospholipid antibodies [APAs], lupus anticoagulant, antithyroid antibodies, and total immunoglobulin levels) are associated with low AMH levels. Analysis of covariance was performed to determine statistical significance of associations. Results: Age of infertile women was 38.6 ± 5.3 years. A total of 50 women (14.2%) had abnormally elevated levels of one or more APA. Even after age adjustments, the presence of at least one APA was significantly associated with a low AMH ( P <.0066). No one specific APA or other immune marker demonstrated an association with AMH. Conclusions: APAs but no other immune markers appear associated with decreased levels of AMH, supporting the hypothesis that non‐specific autoimmunity may adversely affect ovarian reserve.